Regional Economic Outlook, April 2018, Sub-Saharan Africa : Domestic Revenue Mobilization and Private Investment. (Regional Economic Outlook, 2018)
The region is seeing a modest growth uptick, but this is not uniform and the medium-term outlook remains subdued. Growth is projected to rise to 3.4 percent in 2018, from 2.8 percent in 2017, on the back of improved global growth, higher commodity prices, and continued strong public spending. About 3/4 of the countries in the region are predicted to experience faster growth. Beyond 2018, growth is expected to plateau below 4 percent, modestly above population growth, reflecting continued sluggishness in the oil-exporting countries and sustained growth in non-resource-intensive countries. A number of countries (Burundi, DRC, South Sudan, and parts of the Sahel) remain locked in internal conflict resulting in record levels of refugees and Internally Displaced Persons, with adverse spillovers to neighboring countries.